2010
DOI: 10.1071/ch09602
|View full text |Cite
|
Sign up to set email alerts
|

A Regioselective One-Pot, Three Component Synthesis of 6-Aryl-4-cyano-3(2H)-pyridazinones in Water

Abstract: A series of 4-cyano-3(2H)-pyridazinones bearing different aryl substituents in the 6-position of the pyridazinone ring was synthesized regioselectively using a novel efficient one-pot three component reaction of alkyl 2-cyanoacetates with arylglyoxals in the presence of hydrazine hydrate at room temperature in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In continuation of our recent reports on synthesis of pyridazine derivatives, [11][12][13][14][15][16][17][18] here we report the X-ray crystal structure of 3-(4-hydroxy-3-methoxyphenyl)-7,7-dimethyl-7,8-dihydrocinnolin-5(6H)one prepared by reaction of 2-(4-hydroxy-3-methoxyphenyl)-2-oxoacetaldehyde with dimedone in the presence of hydrazine hydrate. 11…”
Section: Introductionmentioning
confidence: 98%
“…In continuation of our recent reports on synthesis of pyridazine derivatives, [11][12][13][14][15][16][17][18] here we report the X-ray crystal structure of 3-(4-hydroxy-3-methoxyphenyl)-7,7-dimethyl-7,8-dihydrocinnolin-5(6H)one prepared by reaction of 2-(4-hydroxy-3-methoxyphenyl)-2-oxoacetaldehyde with dimedone in the presence of hydrazine hydrate. 11…”
Section: Introductionmentioning
confidence: 98%
“…21 These pharmacological and technological properties of pyridazines encourage the development of methods for their synthesis and functionalization. In continuation of our interest in the synthesis of various pyridazine derivatives, [22][23][24][25][26] we decided to investigate the three-component reaction of arylglyoxals, ethyl butyrylacetate and hydrazine hydrate which is extended to the regioselective synthesis of ethyl 6-aryl-3-propylpyridazine-4-carboxylates as a new series of three substituted pyridazines.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, MCRs have emerged as a powerful tool for delivering molecular libraries needed in combinatorial approaches for the assembly and lead identification of bioactive compounds. [21] Based on the above considerations and in continuance of our previous research into the arylglyoxal-mediated synthesis of various heterocycles, [22][23][24][25][26][27][28][29][30][31][32] we have found that 1,3-dialkyl thiobarbituric acids undergo a tandem Knoevenagel-Michael condensation with arylglyoxals leading to the formation of a substituted pyranopyrimidine skeleton. Herein, we report an efficient two-component strategy for synthesis of symmetrically substituted 5-aryloyl-1H-pyrano[2,3-d]pyrimidine 1.…”
Section: Introductionmentioning
confidence: 99%